Synthesis and Antimicrobial Studies of Pyrimidine Pyrazole Heterocycles. (25th August 2014) - Kumar, Rakesh; Arora, Jyoti; Ruhil, Sonam; Phougat, Neetu; Chhillar, Anil K.; Prasad, Ashok K.
Abstract : Prompted from the diversity of the wider use and being an integral part of genetic material, an effort was made to synthesize pyrimidine pyrazole derivatives of pharmaceutical interest by oxidative cyclization of chalcones with satisfactory yield and purity. A novel series of 1, 3-dimethyl-6-hydroxy-2, 4-dioxo-5-(1′-phenyl-3′-aryl-1 H -pyrazol-5′-yl)-1, 2, 3, 4-tetrahydropyrimidines (5a–d ) and 1, 3-diaryl-6-hydroxy-4-oxo-2-thioxo-5-(1′-phenyl-3′-aryl-1 H -pyrazol-5′-yl)-1, 2, 3, 4-tetrahydropyrimidines (5e–l ) has been synthesized. The structures of these compounds were established on the basis of FT-IR, 1 H NMR, 13 C NMR, and mass spectral analysis. All the synthesized compounds were screened for their antimicrobial activity against bacteria and fungi. Among all the compounds, 5g was found to be the most active as its MIC was 31.25  µ g/mL against S. aureus and B. cereus . The compounds5h, 5c, and5e also possess antibacterial activity with MIC values as 62.50, 125.00, and 500.00  µ g/mL, respectively. The compounds5c and5j were found to have antifungal activity against Aspergillus spp. As antifungal drugs lag behind the antibacterial drugs, therefore we tried in vitro combination of these two compounds with standard antifungal drugs (polyene and azole) against Aspergillus spp. The combination of ketoconazole with5c and5j showed synergy at 1 : 8 (6.25 : 50.00  µ g/mL) and 1 : 4 (25 : 100  µ g/mL) against A. fumigatus (ITCC 4517) and A. fumigatus (VPCI 190/96), respectively.